1988
DOI: 10.1038/331168a0
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic shear stress activates a K+ current in vascular endothelial cells

Abstract: The endothelial lining of blood vessels is subjected to a wide range of haemodynamically-generated shear-stress forces throughout the vascular system. In vivo and in vitro, endothelial cells change their morphology and biochemistry in response to shear stress in a force- and time-dependent way, or when a critical threshold is exceeded. The initial stimulus-response coupling mechanisms have not been identified, however. Recently, Lansman et al. described stretch-activated ion channels in endothelial cells and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
506
1
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 924 publications
(526 citation statements)
references
References 21 publications
15
506
1
4
Order By: Relevance
“…Changes in endothelial cells in culture as discussed above may account for these differences, although species differences cannot be ruled out. Shear stress-activated hyperpolarisation has been reported in cultured endothelial cells (Nakache & Gaub, 1988;Olesen et al 1988;Jacobs et al 1995). In aortic strips, changes in the superfusion rate sufficient to evoke their relaxation did not affect membrane potential or the input resistance of the endothelium.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Changes in endothelial cells in culture as discussed above may account for these differences, although species differences cannot be ruled out. Shear stress-activated hyperpolarisation has been reported in cultured endothelial cells (Nakache & Gaub, 1988;Olesen et al 1988;Jacobs et al 1995). In aortic strips, changes in the superfusion rate sufficient to evoke their relaxation did not affect membrane potential or the input resistance of the endothelium.…”
Section: Discussionmentioning
confidence: 94%
“…Cytosolic alkalinisation has been shown to activate NO synthesis (Fleming et al 1994). Shear stress has also been reported to evoke endothelial hyperpolarisation (Nakache & Gaub, 1988) via activation of a K¤ current (Olesen et al 1988). Hyperpolarisation might be transduced to vascular smooth muscle through myoendothelial gap junctions resulting in relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…Les CE possè-dent-elles un tel canal ionique? Il y a une quinzaine d'années, un courant potassique, spécifiquement activé en réponse aux forces de flux, a été détecté dans des CE en culture [23] (Figure 1). Il est fondamental de déterminer quel est le canal ionique responsable de ce courant et de tester sa sensibilité aux forces de flux.…”
Section: Réponses Cellulaires Aux Stimulus Mécaniquesunclassified
“…Whole-cell patch-clamp recordings of single arterial endothelial cells exposed to controlled levels of laminar shear stress in capillary flow tubes demonstrated the evidence for a K + selective, shear stress-activated ionic current [41]. Treatment of endothelial cells with blocking agents to K + channel such as barium chloride or tetraethylammonium inhibited the induction of NO by shear stress and the induced expression of endothelial cell NO synthase (eNOS) and transforming growth factor beta-1 [43,44].…”
Section: K + Channelsmentioning
confidence: 99%
“…Earlier studies have shown that shear stress activates the inward-rectifying K + current leading to cell membrane hyperpolarization [41,42]. Whole-cell patch-clamp recordings of single arterial endothelial cells exposed to controlled levels of laminar shear stress in capillary flow tubes demonstrated the evidence for a K + selective, shear stress-activated ionic current [41].…”
Section: K + Channelsmentioning
confidence: 99%